ETHICAL AND INTERNAL AUDIT RESULTS GAP AT BANK BTPN JEMBER BRANCH - Aulia Ayu Dewinta (Jurnal Mantik, 2022)
Banking as a highly regulated sector must ensure principles of GCG are applied to every aspect of the business. GCG principles like transparency, accountability, responsibility, independence, fairness, and equality. Quality Assurance in the audit process is responsible for reporting and disclosing any violations, including the code of ethics. Ethical principles are very important for internal auditors. Internal auditors often face ethical dilemmas that can challenge them from the standard. This study examines ethical dilemmas and gaps in the work of QA in carrying out audits at Bank BTPN in the Jember area. Phenomenology transcendental Hussler analysis method with two respondents with Noema, Noesis, Epoche, Intentional analysis, and Eidetic Reduction. The results showed that respondents realized that ethical dilemmas deviate from the company's SOPs. To anticipate this, the resource persons are professional, objective, and independent in their assignments. Both establish good communication, maintain emotions politely and openly. The results of the second respondent, ethical dilemmas are understood as inner conflicts, the incidence of denial of findings, the nature of being adamant about being fitting and emotional ties with the auditee are very well understood. To overcome this problem, he works professionally according to existing regulations and with a professional attitude.